The performance of foreign affiliates in German manufacturing: Evidence from a new database - John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
This study presents the first investigation into the performance of foreign - controlled enterprises in German manufacturing based on new micro - data from official statistics. A comprehensive set of performance variables was examined not only by comparing unconditional mean values but also by accounting for other determinants and differences across distributions. The analysis revealed a foreign ownership performance premium with regard to productivity, R&D and export intensities, and average wages. Only profitability did not seem to differ from German - owned enterprises. Results were verified by varying comparison groups of indigenous firms and separating for high- and low-tech sectors. Furthermore, a breakdown by country of origin and type of ownership showed considerable heterogeneity of foreign - controlled affiliates in Germany.
Keywords: F21; F23; 330; foreign ownership; firm performance; inward FDI; multinational enterprise; Verarbeitendes Gewerbe; Multinationales Unternehmen; Auslandsniederlassung; Ausländisch; Unternehmensentwicklung; Schätzung; Deutschland